Pengaruh Etika dan Tekanan Waktu Terhadap Kualitas Audit Keuangan Pemerintah Daerah - Elsa Tandi Sampe; Antong Antong; Erniyati Caronge (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This study aims to analyze the influence of ethics and time pressure on the quality of local government financial audits. This study is motivated by the importance of audit quality in realizing transparency and accountability in public financial management. This research method uses a quantitative approach with a purposive sampling technique on 59 local government auditors. Primary data were collected through questionnaires and analyzed using SPSS. The results of this study indicate that: (1) auditor ethics have a positive and significant effect on audit quality, (2) time pressure has a negative and significant effect on audit quality and (3) auditor ethics and time pressure simultaneously have a significant effect on audit quality. The coefficient of determination (R2) value of 0.847 indicates that the two independent variables are able to explain 84.7% of the variation in audit quality, while 15.3% is influenced by other factors outside this study. This finding confirms that improving audit quality can be achieved through strengthening auditor professional ethics and effective management of time pressure in the implementation of public sector audits.